(untitled) (Research, Society and Development, 2020)
The subject of this case study is the procedures’ analysis used in the rank advancement process in the scope of Centro Estadual de Educação Tecnológica (Technological Education State Center), as well as the way of knowledge sharing among its collaborators (teachers and students), aiming at possible improvements in relation to organizational learning. As a state agency with the mission of promoting professional and technological public education within excellence framework, to intend technological, economic and social development of the state of São Paulo, it is clear, therefore, that its system of rank advancement is envisaged by a set of legal acts. This research premises that the information acquired in such process has not been measured. Organizational learning must take place efficiently. Hence, an online survey was developed for the civil servants of such state agency, in order to gather their opinions regarding the rank advancement process and to question them about other ways to information sharing.